Satisfaction in infrastructure and quality of care in obstetrics-gynecology consultation of a primary care center - Zamora Chávez, Sara Carolina (2016)
Objective: To determine the degree of satisfaction of External Users in Infrastructure and Quality of care of the Surgery Gynecology – Obstetrics service in the “De La Solidaridad” Hospital in Comas. Material and Methods: Anon-experimental observational study was conducted in the service of Gynecology and Obstetrics in the “De La Solidaridad” Hospital in Comas in Lima, Peru with patients of 18 years and up in 249 patients using a anonymous survey, with the modified SERVQUAL instrument, from August 2011 to February 2012. The main outcome was to detect the degree of patient satisfaction. Results: The mean age was 41.41 years (SD 13.36); 74% had incomplete or have not started school. 68.28%. agreed in terms of attention and perception of care. The "explanation with easy words to understand '' had a 73.89% acceptance and the recipe prescribed with clear indications, 75.1% acceptance. Fees had only 25.70% of totally acceptance. 29.72% were rarely agree about the dressing room and 55.75% disagreed with the comfort of the facilities. The perception of quality of care obtained 87.65% agreement. The degree of satisfaction of external users was 72.58%. The degree of satisfaction in relation to infrastructure was 63.58%. Conclusions: The degree of satisfaction of External Users in Infrastructure and Quality of care of the Surgery Gynecology – Obstetrics service in the “De La Solidaridad” Hospital in Comas was high.